HUBUNGAN POLA MAKAN DENGAN PERTUMBUHAN ANAK USIA 1-5 TAHUN - Lucia Ani Kristanti (Jurnal Kesehatan Madani Medika (JKMM), 2019)
Children of today are the future of society. It is important to improve the quality of human beings since childhood – childhood. Results of research conducted by specialists - experts in various regions in Indonesia showed that ⅓ of all children under 5 years of malnutrition . As a result, the child - the child is weak , lethargic , and lower body resistance to infection and consumption of foods that are less qualified nutrition are two factors that affect the growth of children. The researchers' goal was to determine the relationship between the dietary habit and the growth of children aged 1-5 years in Posyandu Kradinan Madiun County. This type of research Analytical. Cross sectional study design. The study was conducted in August 2017. Population taken of all the mothers who have children aged 1-5 years in Posyandu Kradinan Madiun County sample number of 82 respondents and 68 respondents using purposive sampling. The research instrument used questionnaires and KMS. Data were analyzed using chi square. Research, the majority of respondents have a good diet that there were 48 infants (70,6 %). Most respondents, there were 38 infants (55.9 %) had a growth rises. Results of chi square test X2 count is greater than X2 table (7,5>3,841) means that there is a correlation with the growth of the diet of children aged 1-5 years. Expected mothers to provide nutritious food to their children and in order that adequate child nutrition and child can experience growth well.